2018
DOI: 10.1016/j.conbuildmat.2018.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the recycling process and binder type on bituminous mixtures with 100% reclaimed asphalt pavement

Abstract: There is a great interest in increasing the amount of recycled material used in asphalt mixes because of the beneficial impact on the environment. This is leading to the development of different recycling procedures, from cold in-situ to hot in-plant recycling. The objective of the study presented in this paper is to evaluate cracking resistance of recycled mixes manufactured by three types of processes, i.e., cold with emulsion, hot with high penetration bitumens and hot with emulsion (half-warm mixture), usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…grade emulsified bitumen, the average flexural modulus of 5936 MPa was obtained, and an average micro-strain fatigue level of 155 µm/m. Analogous results for 4PB fatigue cracking and fracture properties have been found in several laboratory fatigue studies conducted by different researchers [24,25,80] for a WMA/ HMWA mixture with a total RAP content (100%) and emulsified bitumen.…”
Section: Advanced Mechanical Characterization Of the Mixturesupporting
confidence: 83%
See 1 more Smart Citation
“…grade emulsified bitumen, the average flexural modulus of 5936 MPa was obtained, and an average micro-strain fatigue level of 155 µm/m. Analogous results for 4PB fatigue cracking and fracture properties have been found in several laboratory fatigue studies conducted by different researchers [24,25,80] for a WMA/ HMWA mixture with a total RAP content (100%) and emulsified bitumen.…”
Section: Advanced Mechanical Characterization Of the Mixturesupporting
confidence: 83%
“…For instance, some authors reported that lowering the production temperatures allowed to decrease the RAP aging process of the innermost thin-asphalt layer adhered to the recycled aggregates, thereby obtaining a less stiff and less brittle binder, while avoiding the decrease in its resistance to fatigue cracking [22,23]. To support this, some researchers have shown that mixes with 100% RAP at half-warm temperatures can exhibit similar resistance to fatigue cracking, stiffness, and ductility at three testing temperatures (20 °C, 5 °C, and −5 °C), in comparison with the values expected from conventional HMA mixtures [24], regardless of the failure criterion used for the mechanical analysis (i.e., semi-circular bending (SCB) fracture test, uniaxial tension-compression strain sweep, and indirect tensile fatigue test) [25,26,27,28]. In this line, Lopes et al [29] reported that the addition of RAP improves the fatigue life of such mixtures since the recycled asphalt binder forms a stiff microlayer at the interface of RAP that reduces both the strain and stress concentration within the mixture [30].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, for the HWMRA 100% RAP (2.5%) mixtures with 50/70 pen. grade bitumen, the cracking and fracture properties have been found in other laboratory studies by other researchers (Botella et al, 2016;Nosetti et al, 2018) for a WMA/ HMWA mixture with a total RAP content (100%) and emulsified bitumen. Motter et al, 2015;Pasandín and Pérez, 2013;Pérez et al, 2007;Zhu et al, 2012) for T3 traffic load category (200>AADT≥50).…”
Section: Fatigue Resistancesupporting
confidence: 68%
“…[5] if effective, asphalt pavement reuse results in a substance with properties comparable to those of the typical bituminous mixture. [6] The traditional method for restoring the old bitumen properties of the new (virgin) binder is to rejuvenate the aged asphalt binder. The rejuvenating additive has become one of the recycling agents and is suitable for either highly oxidized mixtures or higher RAP (more than 25% RAP) or recycled asphalt shingles (RAS) mixtures.…”
Section: Introductionmentioning
confidence: 99%